A review of metallurgical slag for efficient wastewater treatment: Pretreatment, performance and mechanism. (20th December 2022) - Ji, Rui; Liu, Tian-Ji; Kang, Le-Le; Wang, Yi-Tong; Li, Jun-Guo; Wang, Fu-Ping; Yu, Qing; Wang, Xiao-Man; Liu, Huan; Guo, Hua-Wei; Xu, Wen-Long; Zeng, Ya-Nan; et al.
Abstract: Metallurgical slag as a by-product of the metallurgical industry not only has huge storage capacity and low price, but also causes serious damage to the environment and threatens the safety of human life by heavy metal in metallurgical slag leaching. The approach of metallurgical slag used to remove pollutants in wastewater is considered to achieve the purpose of "using waste to treat waste". This review focuses on three pretreatment methods of metallurgical slag including acid/alkali pretreatment, mixed pretreatment, and core-shell structure pretreatment, and their structural properties and performance optimization after pretreatment. The removal mechanism of typical pollutants, catalytic performance, reaction conditions, and recyclability of metallurgical slag such as steel slag, blast furnace slag, red mud, copper slag, and manganese slag are summarized and compared. Graphical abstract: Image 1 Highlights: Application of metallurgical slag in the wastewater treatment is summarized. Three pretreatment methods of metallurgical slag are introduced. Structure and performance of pretreated metallurgical slag are compared. The removal mechanisms and influencing factors are introduced. Sustainable utilization of metallurgical slag is discussed.